The impact of unspoken feelings: how communication avoidance leads to mental health in youth - Zahari, Badreena (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2025)
Mental health issues are rising among youth, and one of the underlying but often overlooked causes is communication avoidance. Youth tend to struggle expressing emotions but fail to realize that avoiding communication causes persistent psychological problems. Communication avoidance is a silent killer which eventually leads to emotional suppression and subsequently increases stress, anxiety and depression. Young people typically fail to understand that their mental health progressively deteriorates because of communication avoidance. This study explores how past life experiences and excessive overthinking causes communication avoidance, which will affect mental well-being. The research utilized in-depth interviews as a qualitative method to analyze communication avoidance behaviors in youth between 15 and 30 years old. As a pilot study, this research provides preliminary insights into the link between communication avoidance and mental health, serving as a guide for future studies. The pilot study functions as a foundation to enable real data collection for conducting an organized investigation of this topic. The identification of themes from the pilot study helps in revising research questions and produces more precise data while enhancing the validity of the entire study. Detecting communication avoidance problems represents a critical need because most people are not conscious of its mental health effects on youth. Research addressing communication avoidance problems now will allow investigators to establish specific interventions that promote emotional openness and create conducive environments to enhance mental health.